The importance of playing in the process of including special students in the educational environment (Research, Society and Development, 2021)
Playful activities incorporated into the teaching-learning process of Special education can significantly enhance the construction of knowledge and the cognitive, social and emotional development of special children. In this sense, this study aims to present the view of different authors and teachers from a special school in the city of Porto Alegre, regarding the importance of playing in the process of inclusion of special students in the educational environment. Through a qualitative approach, we first tried to talk about playful activities as fundamental in the formation and socialization of children who are part of Special education. During the work, some bibliographic studies are presented on the pleasure of learning through games and games, making the educational environment more meaningful and pleasurable, facilitating learning, personal, social and cultural development, and the mental health of students /as of Special education. Thus, it is emphasized that recreational activities should be valued and disseminated in all schools as a facilitator and knowledge building tool within the process of inclusion of special students.